Challenges and Opportunities for Therapeutic Targeting of Calmodulin Kinase II in Heart - Nassal, Drew; Gratz, Daniel; Hund, Thomas J. (Frontiers in Pharmacology, 2020)
Heart failure remains a major health burden around the world. Despite great progress in delineation of molecular mechanisms underlying development of disease, standard therapy has not advanced at the same pace. The multifunctional signaling molecule calmodulin kinase II (CaMKII) has received considerable attention over recent years for its central role in maladaptive remodeling and arrhythmias in the setting of chronic disease. However, these basic science discoveries have yet to translate into new therapies for human patients. This review addresses both the promise and barriers to developing translational therapies that target CaMKII signaling to abrogate pathologic remodeling in the setting of chronic disease. Efforts in small molecule design are discussed, as well as alternative targeting approaches that exploit novel avenues for compound delivery and/or genetic approaches to affect cardiac CaMKII signaling. These alternative strategies provide hope for overcoming some of the challenges that have limited the development of new therapies.